Antimicrobial Susceptibility Pattern of Enterococcus Species Isolated From Various Clinical Specimens in a Tertiary Care Center in Western Nepal - Pal, Anjila; Mahawal, Bhim Singh (Journal of Lumbini Medical College, 2021)
Introduction: Enterococcus species are Gram-positive oval cocci arranged in pairs or short chains. They are found as gut microbiota of adults, but from the last decade, they are emerging as causative agents of various nosocomial infections throughout the world. High level aminoglycoside resistance and vancomycin resistance are being increasingly reported from different parts of the world thus limiting the therapeutic options for the treatment of enterococcal infections. The objective of our study was to determine the antimicrobial susceptibility pattern of Enterococcus species isolated from various clinical specimens in Lumbini Medical College and Teaching Hospital, Palpa. Methods: All the clinical samples were cultured and enterococci isolates were tested for antibiotic sensitivity, high level gentamicin resistance and vancomycin resistance by Kirby Bauer disc diffusion method. Results: Among the 90 isolated Enterococcus spp.maximum isolates were obtained from the age group 21-40 years, most from in-patient department with urine as sample (n=53, 58.89%). The highest antimicrobial susceptibility was recorded for linezolid (90.48%) followed by chloramphenicol (79.71%), nitrofurantoin (76.83%) and then high-level gentamicin (70%). The overall prevalence of high level gentamicin resistance and vancomycin resistant enterococci were 30% and 35.55% respectively. Conclusion: The present findings show a high rate of high-level gentamicin and vancomycin resistant enterococci. Thus, routine surveillance of such resistance pattern should be done every year. Linezolid can be considered as a drug of choice to treat serious enterococcal infections.